Hydrometallurgical Recycling of Copper Anode Furnace Dust for a Complete Recovery of Metal Values - Dušan Oráč; Jakub Klimko; Dušan Klein; Jana Pirošková; Pavol Liptai; Tomáš Vindt; Andrea Miškufová (Metals, 2021)
Copper anode furnace dust is waste by-product of secondary copper production containing zinc, lead, copper, tin, iron and many other elements. Hydrometallurgical Copper Anode Furnace dust recycling method was studied theoretically by thermodynamic calculations and the proposed method was verified experimentally on a laboratory scale. The optimum condition for leaching of zinc from dust was identified to be an ambient leaching temperature, a liquid/solid ratio of 10 and H2SO4 concentration of 1 mol/L. A maximum of 98.85% of zinc was leached under the optimum experimental conditions. In the leaching step, 99.7% of lead in the form of insoluble PbSO4 was separated from the other leached metals. Solution refining was done by combination of pH adjustment and zinc powder cementation. Tin was precipitated from solution by pH adjustment to 3. Iron was precipitated out of solution after pH adjustment to 4 with efficiency 98.54%. Copper was selectively cemented out of solution (99.96%) by zinc powder. Zinc was precipitated out of solution by addition of Na2CO3 with efficiency of 97.31%. ZnO as final product was obtained by calcination of zinc carbonates.